Immigrants from the North - Crossland, R. A. (1967)
6s./$1.25; I. The problem of the Indo-Europeans; II. The earliest known Indo-European languages; III. Archaeological evidence for early Indo-European immigration; IV. The region of origin of early Indo-European migrations; V. The impact of the northerners.